The Problem of Syntactic Isoglosses in G. Jahukyan’s Comparative Studies - Gabrielyan, Yuri (Bulletin of Yerevan University B: Philology, 2021)
The paper examines G. Jahukyan’s viewpoint on syntacticisoglosses among the Indo-European languages and particularly between Armenian andthe Celtic languages. In his studies, the scientist puts forward the hypothesis of the VSOtypological sample as being more archaic, which, however, is not definitely evaluated inIndo-European linguistics. The author of this paper confirms G. Jahukyan’s viewpointon the above-discussed matter with the help of careful examination of appropriate factsand also the results of his researches.